The views of European clinicians on guidelines for long‐term follow‐up of childhood cancer survivors. Issue 2 (8th November 2014) - Brown, Morven C.; Levitt, Gillian A.; Frey, Eva; Bárdi, Edit; Haupt, Riccardo; Hjorth, Lars; Kremer, Leontien; Kuehni, Claudia E.; Lettner, Christina; Mulder, Renée L.; Michel, Gisela; Skinner, Roderick; et al.
<x xml:space="preserve">Abstract</x> Background Evidence‐based guidelines are needed to guide effective long‐term follow‐up (LTFU) of childhood cancer survivors (CCS) at risk of late adverse effects (LAEs). We aimed to ascertain the use of LTFU guidelines throughout Europe, and seek views on the need for pan‐European LTFU guidelines. Procedures One expert clinician from each of 44 European countries was invited to participate in an online survey. Information was sought regarding the use and content of LTFU guidelines in the respondent's centre and country, and their views about developing pan‐European LTFU guidelines. Results Thirty‐one countries (70%) responded, including 24 of 26 full EU countries (92%). LTFU guidelines were implemented nationally in 17 countries (55%). All guidelines included recommendations about physical LAEs, specific risk groups and frequency of surveillance, and the majority about psychosocial LAEs (70%), and healthy lifestyle promotion (65%). A minority of guidelines described recommendations about transition to age‐appropriate LTFU services (22%), where LTFU should be performed (22%) and by whom (30%). Most respondents (94%) agreed on the need for pan‐European LTFU guidelines, specifically including recommendations about surveillance for specific physical LAEs (97%), action to be taken if a specific LAE is detected (90%), minimum requirements for LTFU (93%), transition and health promotion (both 87%). Conclusions Guidelines are not universally used throughout Europe. However, there is strong support for developing pan‐European LTFU guidelines for CCS. PanCareSurFup (www.pancare.eu) will collaborate with partners to develop such guidelines, including recommendations for hitherto relatively neglected topics, such as minimum LTFU requirements, transition and health promotion. Pediatr Blood Cancer 2015;62:322–328. © 2014 Wiley Periodicals, Inc.